Features and evolutionary adaptations of the mitochondrial genome of Garuga forrestii W. W. Sm - Chen, Rong; Rao, Rui; Wang, Chun; Zhu, Dongbo; Yuan, Fen; Yue, Liangliang (Frontiers in Plant Science, 2025)
IntroductionGaruga forrestii W. W. Sm. is a tree species of the Burseraceae family, endemic to China, found in hot/warm-dry valleys. This species plays a crucial role in maintaining biodiversity in these ecosystems.MethodsWe performed de novo assembly of the Garuga forrestii mitochondrial genome using PMAT (v.1.5.4), resulting in a typical circular molecule of 606,853 bp. The genome consists of 31 tRNA genes, 3 rRNA genes, 35 protein-coding genes, and 1 pseudogene. The study also investigates RNA editing sites and evolutionary patterns.ResultsThe mitochondrial genome exhibits a low proportion of repetitive sequences (3.30%), suggesting a highly conserved structure. A high copy number of the trnM-CAT gene (4 copies) is noted, which may contribute to genomic rearrangement and adaptive evolution. Among the 476 RNA editing sites, hydrophilic-hydrophobic and hydrophobic-hydrophobic editing events are most common, accounting for 77.10%. Negative selection predominates among most genes (Ka/Ks < 1), while a few genes (e.g., matR, nad3, rps1, rps12, and rps4) show signs of positive selection (Ka/Ks > 1), potentially conferring evolutionary advantages. Additionally, a significant A/T bias is observed at the third codon position. Phylogenomic analysis supports the APG IV classification, with no evidence of horizontal gene transfer.DiscussionThis mitochondrial genome offers valuable insights into the adaptive mechanisms and evolutionary processes of Garuga forrestii. It enhances our understanding of the species' biogeography in tropical Southeast Asia and Southwest China, providing key information on the evolutionary history of this genus.